2014
DOI: 10.1007/s11033-014-3235-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fluorescent advanced glycation end products (AGEs) of human serum albumin upon incubation with 3-β-hydroxybutyrate

Abstract: Advanced glycation end products (AGEs), which are the final products of glycation, have a major role in diabetic complication and neurodegenerative disorders. The 3-β-hydroxybutyrate (3BHB), a ketone body which is produced by the liver, can be detected in increased concentrations in individuals post fasting and prolonged exercises and in diabetic (type I) patients. In this study, the inhibitory effect of 3BHB on AGEs formation by glucose from the human serum albumin (HSA) was studied at physiological condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…However, the concentration of these species in serum and thereby their emission are very low; therefore, the fluorescence of advanced glycation end products (AGEs) having similar spectra was suggested by Münch [19]. Recently, studies on AGEs of human serum albumin by means of circular dichroism, fluorescence spectroscopy and differential scanning calorimetry have been reported by Bohlooli et al [20]. The fluorescence spectra at 325 and 365 nm obtained in our study seem to be similar to those from glycated human serum.…”
Section: Methodsmentioning
confidence: 99%
“…However, the concentration of these species in serum and thereby their emission are very low; therefore, the fluorescence of advanced glycation end products (AGEs) having similar spectra was suggested by Münch [19]. Recently, studies on AGEs of human serum albumin by means of circular dichroism, fluorescence spectroscopy and differential scanning calorimetry have been reported by Bohlooli et al [20]. The fluorescence spectra at 325 and 365 nm obtained in our study seem to be similar to those from glycated human serum.…”
Section: Methodsmentioning
confidence: 99%
“…There are many compounds which have been reported as inhibitors of the glycation process with potential health benefits . Recently, the 3‐β‐hydroxybutyrate (3BHB) has been studied as an inhibitor of fluorescence AGEs formation . It is produced by the liver as a ketone body .…”
Section: Introductionmentioning
confidence: 99%
“…This binding causes extensive protein structural changes [7]. The results of free lysine content assay (TNBSA test) showed that the amount of modified lysine residues in HSA incubated with AA + Glc was significantly greater than that of HSA incubated with Glc and AA alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The third step is the irreversible stage, which produces the AGEs through oxidation, dehydration and cyclization [5]. AGEs are yellow-brown, often fluorescent (some are non-fluorescent), intra- or inter-molecular cross-linked, and insoluble compounds [6], which contribute to pathogenesis of many diseases [7]. …”
Section: Introductionmentioning
confidence: 99%